2002
DOI: 10.1152/ajprenal.00136.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression, localization, and regulation of aquaporin-1 to -3 in rat urothelia

Abstract: . Expression, localization, and regulation of aquaporin-1 to -3 in rat urothelia. Am J Physiol Renal Physiol 282: F1034-F1042, 2002. First published January 29, 2002 10.1152/ajprenal.00136.2001.-Although mammalian urothelia are generally considered impermeable to constituents of urine, in vivo studies in several species indicate urothelial transport of water and solutes under certain conditions. This study investigates the expression, localization, and regulation of aquaporin (AQP)-1, -2, and -3 in ureteral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 26 publications
11
93
0
1
Order By: Relevance
“…Two AQP3 protein bands were detected. One of these appeared at ϳ27 kDa and represented the deglycosylated form of AQP3, whereas the other appeared at ϳ30 -40 kDa and represented a glycosylated form of AQP3 (32,33). This glycosylation is associated with the stability and intracellular translocation of AQP3 but has no influence on water permeability (1,8,35).…”
Section: Resultsmentioning
confidence: 99%
“…Two AQP3 protein bands were detected. One of these appeared at ϳ27 kDa and represented the deglycosylated form of AQP3, whereas the other appeared at ϳ30 -40 kDa and represented a glycosylated form of AQP3 (32,33). This glycosylation is associated with the stability and intracellular translocation of AQP3 but has no influence on water permeability (1,8,35).…”
Section: Resultsmentioning
confidence: 99%
“…Bladders and ureters of anesthetized rats were fixed for immunolocalization by immersion of the tissues in 4% freshly prepared paraformaldehyde in PBS for 1 h. Tissues were then immersed in a cryprotectant solution of 10% EDTA in 0.1 M Tris buffer, pH 7.4, for 1 h at 4°C and frozen on dry ice. Antibodies were immunolocalized on 8-m frozen sections as previously described (30). Sections were incubated overnight at 4°C with primary antibodies diluted to 10 l/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Until now, data about AQPs in the mammalian urinary bladder have been limited. Spector et al [6] investigated the regulation of AQPs in the urothelium of rats following 24 hours of dehydration and water loading tests and reported the localization of AQP1, 2, and 3 in rat urothelium. They suggested that the AQPs in urothelium may play a role in regulating epithelial cell volume and osmolarity.…”
Section: Introductionmentioning
confidence: 99%